2013
DOI: 10.1007/978-3-642-36981-0_14
|View full text |Cite
|
Sign up to set email alerts
|

How Small and Medium Enterprises Are Using Social Networks? Evidence from the Algarve Region

Abstract: Abstract. The evolution of internet created new opportunities for small and medium enterprises (SME), among which are social networks. This work aims at analyzing the potential of these networks for the SME in Algarve, creating a questionnaire for the purpose. The empirical study revealed that some firms have already an integrated business strategy with social networks, as well as a group in the firm responsible for it. Most of their managers consider that social networks enhance performance, but few really me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…Past studies have largely concentrated on the benefits of social media for marketing purposes, by mainly focusing on large firms (Belo et al, 2013;Culnan et al, 2010;Papachristos et al, 2014), leaving aside some key benefits for small enterprises, such as creating value for the firm, in terms of brand recognition and awareness through new Traditional marketing mix strategies that require minimal cost, low barriers to participation and minimal information and technology skills to use (Derham et al, 2011;Nobre and Silva, 2014).…”
Section: Corporate Behaviour and Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have largely concentrated on the benefits of social media for marketing purposes, by mainly focusing on large firms (Belo et al, 2013;Culnan et al, 2010;Papachristos et al, 2014), leaving aside some key benefits for small enterprises, such as creating value for the firm, in terms of brand recognition and awareness through new Traditional marketing mix strategies that require minimal cost, low barriers to participation and minimal information and technology skills to use (Derham et al, 2011;Nobre and Silva, 2014).…”
Section: Corporate Behaviour and Social Mediamentioning
confidence: 99%
“…Whilst prior research on the adoption of social media has demonstrated that large firms are currently able to easily integrate e-commerce and online customer-services (such as collecting complaints) through the social networks, thanks to their financial resources (i.e. assigning to some employees tasks related to the participation to social networks or outsourcing these activities to another firm specialized in this area) (Culnan et al , 2010), other ones have provided evidence about the slow adoption process due to the negative perception of social media usefulness, unfamiliarity with the technology, difficulties in measuring the effect of these strategies on firm’s performance and the lack of resources devoted to the development of plans (both strategic and operational) based on social media (Belo et al , 2013; Papachristos et al , 2014).…”
Section: Corporate Behaviour and Social Mediamentioning
confidence: 99%
“…Por otro lado, para esta segunda categoría se identificó los siguientes hallazgos clave en esta revisión: En primera instancia, los modelos de ingresos que se basan en la publicidad son más apropiados en el canal web e indican que la tendencia actual está dirigida hacia las estrategias de marketing en redes sociales en reemplazo de la publicidad tradicional [20]. Por consiguiente, para mantener la competitividad empresarial, se han adaptado nuevas características como empresas virtuales, diseños creativos, redes sociales y plataformas virtuales, de igual manera hay dos formas del uso de las redes sociales, la primera es para la interacción y el conocimiento de producto-cliente y la segunda es sobre la potencia del marketing [21]. También, las acciones en las redes sociales son un elemento importante en la actividad de las empresas y pymes, por lo tanto, esto implica poseer las habilidades necesarias para crear una red de contactos, que a la vez funcione como una comunidad para los consumidores [22].…”
Section: Discussionunclassified
“…Los motores de cambio modernos han dado lugar a nuevas características para mantener la competitividad empresarial: empresas virtuales, diseño creativo, redes sociales, plataformas móviles, etc. ; asimismo, se identificó dos dimensiones del uso de las redes sociales: redes sociales para la interacción y el conocimiento producto-cliente; y redes sociales con potencial de marketing [21].…”
Section: Medios De Difusiónunclassified
“…Uses of social media extend beyond simply connecting people (Belo et al, 2013). SMEs use social media platforms for business functions such as market research, customer acquisition, marketing, and customer support (Culnan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%